Pemberdayaan Masyarakat Desa Tadukan Raga melalui Budidaya Jamur Merang dan Maggot BSF untuk Pengolahan Limbah Perkebunan Bernilai: indonesia - Bako, Ilham Perkasa; Sidabutar, Rivaldi; Al Fath, Muhammad Thoriq; Dalimunthe, Nisaul Fadilah; Buysang, Luke Gilbert; Vella, Radia; Vannes, Vannes (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Community service aims to provide tangible contributions by offering innovative solutions to various local problems. One of Indonesia’s major issues, especially in urban areas, is waste management. Every day, tons of waste are produced, but it is often disposed of without further processing. A lack of public knowledge about organic waste management is a key contributing factor. In Tadukan Raga Village, Deli Serdang Regency, Universitas Sumatera Utara implemented a community service program to educate residents on environmentally friendly organic waste processing using maggots. Maggots can decompose organic waste and produce residue that serves as fertilizer, while the larvae themselves are valuable as fish feed. Additionally, residents were trained in straw mushroom cultivation to maximize the benefits of organic waste. The program successfully increased public awareness of waste management, produced economically valuable products, and established maggot-based production facilities. This initiative not only reduced environmental impact but also supported local economic sustainability. Recognizing further potential for development, additional training continues to be conducted to strengthen the program’s outcomes.